ANALISIS SUPERVISI KLINIS PENGAWAS DALAM MENINGKATKAN KOMPETENSI MANAJERIAL KEPALA SEKOLAH DASAR NEGERI DI KECAMATAN MEGANG SAKTI: ANALISIS SUPERVISI KLINIS PENGAWAS DALAM MENINGKATKAN KOMPETENSI MANAJERIAL KEPALA SEKOLAH DASAR NEGERI DI KECAMATAN MEGANG SAKTI - Agita Ryza Kusuma (Improvement: Jurnal Ilmiah untuk Peningkatan Mutu Manajemen Pendidikan, 2020)
This thesis analyzes the supervisors' clinical supervision in enhancing the managerial competence of the principals of public primary schools in the district of Megang Sakti. The purpose of this study was to analyze the supervisors' clinical supervision in enhancing managerial competence of public elementary school principals in the district of Megang Sakti in terms of the role of supervisors, supervisors guidance, and improvement of the principal's managerial competence after clinical supervision. The method used in this study is descriptive qualitative data collection techniques using observation, interviews, and documentation. The location of this research was conducted at the supervisory office in the education sector of Megang Sakti sub-district and in five public elementary schools in Megang Sakti sub-district. The subjects in this study were two supervisors, five school principals, and five public elementary school teachers in the district holding the magic. The conclusion of this research is related to the role of supervisors in providing services to school principals need to conduct an intensive evaluation of supervision conducted both structured and systematic. The analysis related to supervisors conducted by supervisors is viewed from the aspects of supervising, guiding, monitoring, coordinating, and evaluating supervisors, but the methods and strategies have not been optimal, so they must be improved to be more optimal, especially in the aspects of guiding, evaluating and following up. Clinical supervision by supervisors in increasing the managerial competence of school principals has increased, but there is a need for evaluations and follow-up for supervisors regarding supervisors' methods and strategies in conducting guidance to school principals.